Immunoreactive Cells After Cerebral Ischemia - Wang, Yijie; Zhang, John H.; Sheng, Jifang; Shao, Anwen (Frontiers in Immunology, 2019)
The immune system is rapidly activated after ischemic stroke. As immune cells migrate and infiltrate across the blood-brain barrier into the ischemic region, a cascade of cellular and molecular biological reactions occur, involving migrated immune cells, resident glial cells, and the vascular endothelium. These events regulate infarction evolution and thus influence the outcome of ischemic stroke. Most immune cells exert dual effects on cerebral ischemia, and some crucial cells may become central targets in ischemic stroke treatment and rehabilitation.